KUALIFIKASI PENGAJAR ALKITAB MELAWAN AJARAN SESAT ANTI- TRITUNGGAL BERDASARKAN 1 TIMOTIUS 4:1-16 - Franseda Sihite (Phronesis: Jurnal Teologi dan Misi, 2023)
Heresy teachings that reject the doctrine of the Triune God (anti-Trinity) have emerged since the beginning of Christianity in the world. The form exists in various variants, in principle, denying God's divinity and personal equality existing in the Trinity. New variants, such as Oneness Pentecostalism and Dwitunggal teachings, are still emerging in the current global era. Anti-Trinity teachings are a threat to lead the church astray. A Bible teacher needs to have special qualifications to combat anti-Trinitarian teachings. What qualifications are needed for a Bible teacher against anti-Trinitarian teachings as stated in 1 Tim? 4:1-16 is the research question asked. For this reason, this scientific article was written to explain these qualifications. By using exegesis and literature study methods, it was found that the qualifications that a Bible teacher should have against Anti-Trinitarian teachings are living out the teachings of the apostles by adhering to them and faithfully teaching them, having biblical spiritual-theological competence by understanding the basic principles of the Christian faith (Basic Beliefs), has Pneumatic Inspirational Hermeneutics, and can monitor himself and his teachings.